1997
DOI: 10.1016/s0014-5793(97)01068-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of caspase activity by hydrogen peroxide: implications for apoptosis

Abstract: The induction of apoptosis in Jurkat T-lymphocytes with 50 μΜ hydrogen peroxide was associated with caspase activation. Caspase activity was first detected 3 h after treatment, and the morphological features of apoptosis were apparent by 6 h. At higher concentrations of hydrogen peroxide there was no detectable caspase activity, and the cells died by necrosis. Cells treated with hydrogen peroxide were impaired in their ability to undergo Fas-mediated apoptosis. This appeared to be the result of direct inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
391
1
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 618 publications
(424 citation statements)
references
References 20 publications
27
391
1
5
Order By: Relevance
“…This study and other studies have shown the redox modification of caspase activity through the use of oxidants such as peroxide 40 (and Figure 4), diamide 59 and the dithiocarbamate disulfides. 60 It is becoming evident that the cellular reducing environment maintained by endogenous antioxidants such as glutathione and thioredoxin 59 plays an important role in the ability of the caspases to execute the effector stages of the apoptotic program.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This study and other studies have shown the redox modification of caspase activity through the use of oxidants such as peroxide 40 (and Figure 4), diamide 59 and the dithiocarbamate disulfides. 60 It is becoming evident that the cellular reducing environment maintained by endogenous antioxidants such as glutathione and thioredoxin 59 plays an important role in the ability of the caspases to execute the effector stages of the apoptotic program.…”
Section: Discussionsupporting
confidence: 63%
“…38 This, together with studies demonstrating the sensitivity of caspases to redox state alterations, 40 suggested that the inactivation of caspase-3 during retinal cell apoptosis may be due to oxidative modification. Figure 4A demonstrates the ability of peroxide to inactivate the caspase activity in a cytosolic extract from anti-Fas IgM treated Jurkat cells.…”
Section: Caspases Are Oxidatively Inactivated During Retinal Cell Deathmentioning
confidence: 99%
“…However, mounting evidence, including the results presented herein, is showing that tightly regulated ROS can subsequently regulate caspases, 21 phosphatases 19 and Ras itself. 18 Man-A caused a large induction ( 12-fold) of AEO 2 2 in WEHI-231 lymphoma cells, but much weaker responses were noted in the A20.2J lymphoma and in Du145, human prostate cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…An emerging body of evidence is revealing that ROS can mediate and regulate finely tuned biochemical responses. [17][18][19][20][21] Therefore, because the tumor cells underwent apoptosis, we explored the impact of Man-A-stimulated ROS on cellular caspase activation and the influence of ROS on the Ras/MEK/ERK and Ras/PI3K/Akt signaling systems, which are known to impart growth and survival advantages on tumor cells.For the first time, our data show that Man-A-stimulated ROS participate in caspase activation, the dephosphorylation of Akt, Raf, MEK and ERK, and specific cleavage of MEK and Akt, but not of ERK. Furthermore, Man-A deactivated Ras signaling effectors without inhibiting Ras activity.…”
mentioning
confidence: 99%
“…At higher concentrations (4200 mM), H 2 O 2 inhibits the activation of caspases and rather induces necrosis. 30 H 2 O 2 also inhibits the activation of recombinant caspases suggesting that the caspase inhibitory effect is dependent on direct interference with caspase activity. 31 Therefore, it might well be that APIT produces levels of H 2 O 2 that damage the cell but prevent apoptosis by blocking caspase function.…”
Section: Discussionmentioning
confidence: 99%